Haematobia exigua: its association with and significance to the buffalo husbandry - M. Fadzil,; Ragawan, K (Malaysian Society of Parasitology and Tropical Medicine, 1985)
The number of Haematobia exigua caught in a 30-minute trapping averaged 55.25. The volume of blood ingested averaged 1.4 .mu.l per fly. Feeding rate was 89 percent